Filsafat Tao sebagai Kritik Ekologis atas Krisis Lingkungan Poco Leok - Fernandes Fernando (Pusat Riset dan Inovasi Nasional, 2025)
The global environmental crisis is increasingly alarming, with deforestation and resource exploitation severely impacting ecosystems and local communities. In Indonesia, Flores Island has become a strategic site for geothermal projects, including the planned drilling in Poco Leok, Manggarai, East Nusa Tenggara. This project has provoked strong resistance from local communities due to ecological threats such as deforestation, biodiversity loss, water pollution, and water scarcity, all of which exacerbate social vulnerability, particularly among women. This study employs a qualitative literature-based analysis using Taoist philosophy as an interpretive framework. The principles of Yin–Yang, Wu Wei, and Ziran are applied as reflective lenses to identify the root of the crisis: the imbalance in human–nature relations caused by exploitative and dominant development models. The findings demonstrate that economy-driven development undermines ecological harmony and local wisdom, thereby deepening social hardship. In contrast, Taoist philosophy offers an alternative paradigm that emphasizes balance, harmony, and respect for the natural order. Addressing the Poco Leok conflict therefore requires not only a reassessment of policy but also a paradigm shift in development toward ecological justice and inclusive, sustainable well-being.